2008
DOI: 10.1111/j.1939-1676.2007.0005.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CCNU and DTIC Chemotherapy for Treatment of Resistant Lymphoma in Dogs

Abstract: Background: Pleotropic-glycoprotein (P-gp)-mediated resistance is the usual cause of relapse in dogs with lymphoma. 1-(2-chloroethyl)3-cyclohexyl-1-nitrosurea (CCNU) and 5-(3,3-dimethyl-1-triazeno)-imidazole-4-carboxamide (DTIC) are alkylating agents that are not affected by P-gp and lack cross-resistance to each other. A combination protocol offers the advantage of improved summation dose and synergistic activity.Hypothesis: A combination of CCNU and DTIC that is well tolerated can be used to treat dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Previous studies have identified that the inclusion of multiple alkylating agents within chemotherapy protocols to treat canine multicentric lymphoma results in the T-cell phenotype no longer being a negative prognostic factor. 29,30 Mild toxicosis was fairly common with MOPP with 76% of the dogs experiencing at least 1 episode of hematologic toxicosis and 78% of the dogs experiencing at least 1 episode of gastrointestinal toxicosis. The most clinically relevant toxicosis was neutropenia, which was considered moderate to severe in 38% of the cases in which it was documented.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that the inclusion of multiple alkylating agents within chemotherapy protocols to treat canine multicentric lymphoma results in the T-cell phenotype no longer being a negative prognostic factor. 29,30 Mild toxicosis was fairly common with MOPP with 76% of the dogs experiencing at least 1 episode of hematologic toxicosis and 78% of the dogs experiencing at least 1 episode of gastrointestinal toxicosis. The most clinically relevant toxicosis was neutropenia, which was considered moderate to severe in 38% of the cases in which it was documented.…”
Section: Discussionmentioning
confidence: 99%
“…In a total of 72 previously reported cases, the mean age at the moment of diagnosis was 8. Evidences of renal toxicity, such as azotemia, polyuria, and polydipsia, are also reported, but usually to a lesser degree (HEADING et al, 2011;FLORY et al, 2008). In this study, although there were no complaints of clinical symptoms related to renal failure, increased values of urea (VCOG-CTCAE grade 1) and creatinine (VCOG-CTCAE grade 2) were observed in 66.6% (10/15) and 40% (6/15) ab Different letters in a row indicate significant difference (P Significant differences in serum levels of urea and urine density were observed between M1 and M2, thus suggesting the potential deleterious effects of the use of lomustine in the evaluated dogs (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Median TTP for dogs achieving complete remission (CR) was 63 days versus a median TTP of 47 days in dogs achieving partial remission (PR). In 2008, Flory et al 9 reported an ORR of 35% in dogs with resistant lymphoma treated with the combination of lomustine and dacarabazine as a rescue protocol. Median TTP for dogs achieving CR was 83 days versus a median TTP of 25 days in dogs achieving PR.…”
mentioning
confidence: 99%